IMPLEMENTASI ROBOT LINE FOLLOWER PENYIRAM TANAMAN OTOMATIS MENGGUNAKAN METODE PROPORTIONAL–INTEGRAL–DERIVATIVE CONTROLLER (PID) - Muhammad Yusuf; Isnawaty Isnawaty; Rahmat Ramadhan (semanTIK, 2016)
The use of robots can be applied in  plant  watering vegetables, fruits and flowers using the greenhouse system. Greenhouse system is not affected by rainfall so that the robot can be used for watering plants that perform settings using time as a command to do the watering. The method used to control a robot that is PID (ProPortional language of abbreviations  - Integral  -  Derivative controller) is a controller to determine the precision of the instrumentation system with the characteristics of their feedback on the proficiency level system. PID control component consists of three types: ProPortional, Integrative and Derivative. All three can be used together or individually depending on the response we wanted to a plant. The working principle of robot watering is done by detecting robot lines as the future path of robotic automation. Line search performed by detecting the light emitted by the LED and read by the sensor Photodioda. To follow the line of the robot are driven by a DC motor which is controlled using PID method, the robot moves automatically using the application of a DC motor. Robot uses sensor readings Photodioda to do watering, after the robot detects an intersection on the path the robot will stop and turn on the water pump to do the watering and if the robot was doing the watering according to what was ordered by the program the robot will toward the place dismissal is to detect fork in the path. Keywords— Robot, Line Follower, PID, Automated Watering Plants